Ultrafast charge transfer in MoS2/WSe2 p–n Heterojunction. (6th May 2016) - Peng, Bo; Yu, Guannan; Liu, Xinfeng; Liu, Bo; Liang, Xiao; Bi, Lei; Deng, Longjiang; Sum, Tze Chien; Loh, Kian Ping
Abstract: Atomically thin and sharp van der Waals heterojunction can be created by vertically stacking p-type monolayer tungsten diselenide (WSe2 ) onto n-type molybdenum disulfide (MoS2 ). Theory predicts that stacked MoS2 and WSe2 monolayer forms type II p–n junction, creating a built-in electric field across the interface which facilitates electron–hole separation and transfer. Gaining insights into the dynamics of charge transfer across van der Waals heterostructure is central to understanding light-photocurrent conversion at these ultrathin interfaces. Herein, we investigate the exciton dissociation and charge transfer in a MoS2 /WSe2 van der Waals hetero-structure. Our results show that ultrafast electron transfer from WSe2 to MoS2 take place within 470 fs upon optical excitation with 99% charge transfer efficiency, leading to drastic photoluminescence quenching and decreased lifetime. Our findings suggest that van der Waals heterostructure may be useful as active components in ultrafast optoelectronic devices.